Does Government Fragmentation and Fiscal Decentralization Constrain Leviathan? New Evidence From Indonesia Experience - Aan Zulyanto; Lilis Siti Badriah (EKO-REGIONAL, 2024)
Since the reform era in 1999, Indonesia has made a regional expansion policy and widespread fiscal decentralization policy. During the 1999-2014 period, Indonesia's autonomous regions increased by 70 percent compared to the previous period. Based on the Leviathan hypothesis, the two policies should create a competitive climate and increase the efficiency of government spending. This study aims to analyze the application of the Leviathan hypothesis in the policy of regional expansion and fiscal decentralization in Indonesia. The study uses panel data regression from 32 provinces during the 2002-2020 period. The study results show that the Leviathan hypothesis does not apply to Indonesia's regional expansion and fiscal decentralization policies. This condition happened because the division of regions in Indonesia was caused more by political interests. Most regional revenues still depend on transfers from the central government. The results of this study imply that to obtain tangible benefits from regional expansion, a thorough understanding of regional economic potential is needed, and the need to improve the quality of human resources to optimally utilize regional potentials so that regional independence will be created.